Sosialisasi Pengelolaan Sampah Plastik di Kawasan Wisata Pantai Tanjug Kasuari Kota Sorong - Murni; Abu, Nur; Marshus, Ummi Hanifah; Hilmansyah, Hilmi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Tanjung Kasuari Beach is one of the famous beach attractions in Sorong City, Papua Barat Daya, and has an unspoiled natural atmosphere. Plastic waste management in the Tanjung Kasuari beach area aims to increase public awareness regarding the negative impact of plastic waste on the environment and the importance of keeping beaches clean. Plastic waste management is a priority program based on the condition of the most abundant and frequently encountered piles of plastic waste. Therefore, local people and tourists will better understand the negative impact of plastic waste on the environment. It can also encourage reducing the amount of plastic waste thrown away carelessly, thereby reducing pollution in coastal areas. In this way, the beach will become more beautiful for tourists, positively impacting the local tourism sector.